The local range of natural cosmetics: Consumer perceptions and assessments in Germany - Julia Ruf; Klaus Menrad; Agnes Emberger-Klein (Business Strategy and the Environment, 2024)
Natural cosmetics offer the opportunity to reduce the environmental burden caused by the consumption of cosmetic products. This qualitative study analyzes the local range of natural cosmetics and related consumer perceptions and assessments in two case cities in Germany by applying a mixed-method approach of store checks and the photovoice method. Results of the study show that there is only a limited match of the actual range and consumer perception for some types of retail businesses and a mismatch for product categories. Additionally, participants showed little awareness of the most common natural cosmetic certifications. Consumer assessments about the range of natural cosmetics were influenced by factors such as the arrangement of products in the shops and consumers' experience and knowledge about natural cosmetic brands. Retailers can use the study results in arranging natural cosmetics accordingly; companies can use it to emphasize branding, and policy-makers can increase consumer knowledge about natural cosmetics.
Keywords: 330; bio-based products; consumer perceptions and assessments; green cosmetics; local range; natural cosmetics